2010
DOI: 10.1007/s10237-010-0216-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of in vivo human skin using a 3D force-sensitive micro-robot and finite element analysis

Abstract: The complex mechanical properties of skin have been the subject of much study in recent years. Several experimental methods developed to measure the mechanical properties of skin in vivo, such as suction or torsion, are unable to measure skin's anisotropic characteristics. An experiment characterising the mechanical properties of in vivo human skin using a novel force-sensitive micro-robot is presented. The micro-robot applied in-plane deformations to the anterior forearm and the posterior upper arm. The behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 38 publications
2
62
0
Order By: Relevance
“…4) align most closely with the long axis of the forearm. Flynn et al [28] demonstrated that although the proximal-distal axis of the arm produced the stiffest response, the perpendicular direction did not produce the least stiff response, which was found at 60 deg from the long axis. Likewise, we found the lowest modulus in direction 2, rather than the approximately perpendicular orientation of direction 3 relative to the long axis of the arm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4) align most closely with the long axis of the forearm. Flynn et al [28] demonstrated that although the proximal-distal axis of the arm produced the stiffest response, the perpendicular direction did not produce the least stiff response, which was found at 60 deg from the long axis. Likewise, we found the lowest modulus in direction 2, rather than the approximately perpendicular orientation of direction 3 relative to the long axis of the arm.…”
Section: Discussionmentioning
confidence: 99%
“…A three-axis microrobot, similar to that of Flynn et al [28] shown in Fig. 1, underwent modifications to its force transduction and timing hardware so that stochastic system identification techniques could be implemented to characterize the dynamic mechanical properties of human skin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the possibilities for in vivo testing are limited by technical feasibility oand by ethical considerations. When attempts are made at characterising human skin in vivo through mechanical means (stretching (13,14), suction (15,16,17), torsion (18,19), indentation (20), etc. ), the skin is distorted, rotated and/or stretched, which briefly deforms the collagen fibre network and thus, significantly affects the accuracy of the experimental measurements.…”
Section: Introductionmentioning
confidence: 99%